Characterization of the Polycomb-Group Mark H3K27me3 in Unicellular Algae - Mikulski, Pawel; Komarynets, Olga; Fachinelli, Fabio; Weber, Andreas P.M.; Schubert, Daniel (Frontiers in Plant Science, 2017)
Polycomb Group (PcG) proteins mediate chromatin repression in plants and animals by catalyzing H3K27 methylation and H2AK118/119 monoubiquitination through the activity of the Polycomb repressive complex 2 (PRC2) and PRC1, respectively. PcG proteins were extensively studied in higher plants, but their function and target genes in unicellular branches of the green lineage remain largely unknown. To shed light on PcG function and modus operandi in a broad evolutionary context, we demonstrate phylogenetic relationship of core PRC1 and PRC2 proteins and H3K27me3 biochemical presence in several unicellular algae of different phylogenetic subclades. We focus then on one of the species, the model red alga Cyanidioschizon merolae, and show that H3K27me3 occupies both, genes and repetitive elements, and mediates the strength of repression depending on the differential occupancy over gene bodies. Furthermore, we report that H3K27me3 in C. merolae is enriched in telomeric and subtelomeric regions of the chromosomes and has unique preferential binding toward intein-containing genes involved in protein splicing. Thus, our study gives important insight for Polycomb-mediated repression in lower eukaryotes, uncovering a previously unknown link between H3K27me3 targets and protein splicing.